Trends in Meteorological Drought in Iran Using the SPI Index and Mann-Kendall Test: A Review (Journal of Asian Geography, 2025)
Drought is one of the most significant climatic hazards in Iran, occurring with varying intensity and frequency due to the country's wide geographical and climatic diversity. Investigating drought trends can offer valuable information for sustainable water resource management and reducing vulnerability in the agricultural sector. This review aims to systematically evaluate research conducted on the trend of meteorological droughts in Iran, focusing on the Standardized Precipitation Index (SPI) and the non-parametric Mann-Kendall (MK) test. In this study, 13 related articles were used and analysed, and data for the SPI index from 1951 to 2019 were reviewed. Most arid and semi-arid regions have experienced decreases in precipitation and increases in drought severity, whereas northern and humid regions exhibit more variable and less predictable behaviour. Overall, evidence suggests that the intensity and frequency of droughts have increased in recent decades, emphasizing the importance of climate adaptation policies and water resources management.